PENGARUH KUALITAS PELAYANAN DAN HARGA MELALUI KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA NUGROHO VIATAMA PEST CONTROL SEMARANG) - Dany Krispiandhita; Handoyo Djoko Waluyo; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2015)
The competition with other pest control service offering similar service results in the decreasing number of customers at NUGROHO VIATAMA Pest Control Semarang. Within the past three years (2011-2014). This study is aimed at finding out the influence of price and service quality upon customer loyality mediated by customer satisfaction. A 90 customers are chosen using purposive sampling method. Data are obtained by using questionnaire, interview, observation and documentation which are then analyzed using path analysis. The study concludes that price and service quality have bigger direct impact upon customer loyalty than the indirect impact.Total impact of price upon customer loyalty is bigger that total impact of service quality upon loyality. Nugroho Viatama Pest Control, Semarang must continue to improve the quality of service that has been held today. In addition it must constantly strive to reduce the price in order to win the competition with other similar companies.